Local Moho distribution in the eastern Mediterranean region from gravity inversion: eastern Mediterranean Sea - Harash, Fayez; Khalaf, Amin; Al-Ansari, Nadhir; Chen, Chao; Alrawi, Imad; Al-Khafaji, Harith; Tageldin, Mohammed (Frontiers in Earth Science, 2023)
This paper discusses the variations of Moho surface inverted from Bouguer gravity data beneath the northwestern of the Arabian plate. The results obtained by applying 3DINVER program developed in MATLAB environment using the Parker-Oldenburg method. The calculation results show that the maximum Moho depth observed in the western Arabian shield part ranges between 40 km and 48 km, and the minimum values of 10 to 20 km mainly concentrated beneath the Mediterranean Sea. The unique part of this study is the exponential density contrast decrease in the of sediments- basement in the Syrian part. The gravity anomaly of the sediments is computed using a density contrast varies exponentially with depth. To validate our inverted results, we compared it to seismic results that showed good agreement with our results.